An atomistic study on the mechanical behavior of bamboo cell wall constituents. (15th October 2018) - Hao, Huali; Tam, Lik-ho; Lu, Yang; Lau, Denvid
Abstract: Although the bamboo material has excellent mechanical properties, the anisotropic mechanical properties across and along the bamboo culm hinder its use as the structural material. As the bamboo fibers are the source of the mechanical properties for bamboo, a fundamental understanding on the structure and mechanical behaviors of bamboo fiber and its constituents enables us to figure out the origin of the anisotropic mechanical properties. In this work, the mechanical response of the cellulose, hemicellulose, and lignin under uniaxial tensile at the strain rate of 10 8 s −1 is investigated by molecular dynamics simulation and the molecular conformational change under the tensile deformation is in situ captured. The breakage of the hydrogen bonds and slippage of the linear polymer chains are dominant for the failure of the cellulose. The normal stress dominated fracture mechanism is the key to the failure of the hemicellulose whereas the shear stress dominated fracture mechanism is the main failure mode for the lignin. The revealed relationship between the structure and mechanical properties of the cell wall constituents in bamboo fibers provides a guideline for assembling of the basic constituents and for modifying their structure to obtain a material that has isotropic mechanical properties and maintains the excellent mechanical properties of the bamboo. Graphical abstract: Image 1 Highlights: Structural evolution of bamboo constituents during tensile deformation is studied. The tensile stress controls the failure of hemicellulose with branched chains. The shear stress dominates the failure of lignin with crosslinked chains. Our work lays a foundation to figure out the mechanical behavior of bamboo fiber.